2017
DOI: 10.18632/oncotarget.16626
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acids inhibit migration in breast cancer cells by inhibition of NEMO sumoylation and NF-κB activity

Abstract: Ginkgolic acids (GA), a group of alkyl phenols found in crude extracts of Ginkgo biloba leaves, are known to have anticancer activity, but their mode of action is not well understood. Our aim in this study was to investigate the anti-migratory activity of seven GA against breast cancer cells and to determine the molecular mechanism behind this activity. All seven GA and their mixture inhibited wound healing in MCF-7 and MDA-MB 231 breast cancer cells. None of the compounds nor the mixture showed cytotoxicity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
(62 reference statements)
1
40
0
1
Order By: Relevance
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Collectively, the results of the present study indicated that GA suppressed the development of RCC. These results were consistent with previous studies demonstrating that GA plays an inhibitory biological role in cancer (12)(13)(14)(15)25). However, the biological effect of GA on RCC was observed at high concentrations of GA in vitro and it is uncertain whether this concentration would be possible in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Extracts from natural plants are becoming an increasingly popular strategy to identify novel antitumor compounds (23,24). Recently, several studies have reported that GA displays promising antitumor activities (12)(13)(14)(15). Therefore, identification of the regulatory mechanism of GA in tumorigenesis would provide valuable insight for the treatment of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C15:1 is one of the most abundant GAs in Ginkgo biloba L. extract (14). Recently, a number of studies have indicated the anticancer activity of GA in a variety of cancer types and the less toxic reaction on non-cancerous cells (15)(16)(17)(18). However, to the best of our knowledge, whether GA can inhibit the invasion of liver cancer cells and the underlying mechanisms remains unknown.…”
Section: Introductionmentioning
confidence: 99%